Band Gap Formation In A Beam With Attached Local Resonators And Periodically Arranged Intermediate External Supports - Ghazaryan, K.; Piliposyan, G. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In the paper a comparative study of a band gap formation mechanism is presented in finite and infinite homogeneous beams rested on periodically arranged intermediate external supports and periodically attached local mass-spring resonators. The transfer matrix method in conjunction with Bloch-Floquet’s approach is extended to study the flexural wave vibration and phonon band gaps generated by both of external intermediate supports and local resonators. The eigenvalue vibration problems are formulated for pinned and clamped multi-span finite length beams and the equation defining eigen frequencies are obtained. The novelty of the paper is the analytical and numerical results concerning formation of band gaps caused by local resonators and intermediate external supports. Աշխատանքում ներկայացված է պարբերաբար տեղակայված միջանկյալ արտաքին հենարաններին հենված և տեղային ռեզոնատորներով միացված հեծանում հաճախությունների արգելված գոտիների կազմավորման համեմատական վերլուծությունը: Տրանսֆեր մատրիցների մեթոդի հետ զուգակցված, Բլոխ-Ֆլոկեի տեսության շրջանակում հետազոտված է արգելված գոտիների գոյացման մեխանիզմները՝ պայմանավորված ինչպես հենարաններով, այնպես էլ ռեզոնատորներով: Ձևակերպվել են եզրային խնդիրները և ստացվել են ամրակցված և հոդակապորեն հենված վերջավոր երկարության բազմաթռիչք հեծանների սեփական արժեքները որոշող հավասարումները: В работе представлен сравнительный анализ механизма образования запретных зон частот в балке с присоединенными локальными резонаторами и опертой на периодически расположенные промежуточные внешние опоры. В рамках теории Блоха-Флоке в сочетании метода трансфер матриц исследован механизм образования запретных зон, генерируемых как опорами так и резонаторами. Сформулированы краевые задачи и получены уравнения определяющие собственные частоты защемленных и шарнирно опертых многопролетных балок конечной длины.
Keywords: Механика деформируемых тел; Упругость